2019
DOI: 10.1111/cod.13294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro testing strategies for hazard assessment of the skin sensitization potential of “real‐life” mixtures: The case of henna‐based hair‐colouring products containing p‐phenylenediamine

Abstract: Background: Allergic contact dermatitis caused by henna-based hair-colouring products has been associated with adulteration of henna with p-phenylenediamine (PPD).Objectives: To develop a testing approach based on in vitro techniques that address key events within the skin sensitization adverse outcome pathway in order to evaluate the allergenic potential of hair-colouring products. Methods:The following in vitro assays were used to test the sensitizing capacity of hair dye ingredients: the micro-direct peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…In addition, we observed enhanced reactivity of SWNTs, TiO 2 , and C 60 to Cys as compared with Lys peptides. Studies focused on characterization of materials with skin sensitization potential have reported the tendency of sensitizing agents to deplete Cys 15,26‐28 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed enhanced reactivity of SWNTs, TiO 2 , and C 60 to Cys as compared with Lys peptides. Studies focused on characterization of materials with skin sensitization potential have reported the tendency of sensitizing agents to deplete Cys 15,26‐28 …”
Section: Discussionmentioning
confidence: 99%
“…HaCaT human immortalized keratinocytes, obtained from the Rio de Janeiro Cell Bank (Brazil), were first used to perform the cytotoxicity analysis to obtain noncytotoxic concentrations of each test material that maintain cell viability ≥80% (CV 80 ) . Cells, previously seeded overnight in cell culture flasks (25 cm 2 ) at 1.5 × 10 5 cells/mL, were then exposed to each test material at noncytotoxic concentrations (CV 80 ) for 4 hours for gene expression analysis, based on previously described treatment protocol .…”
Section: Methodsmentioning
confidence: 99%
“…Our group has demonstrated that adulteration of henna products with the potent contact allergen p ‐phenylenediamine (PPD) changes the toxicological profile of henna by modulation of the keratinocyte and dendritic cells network involved in skin sensitization . To better understand the keratinocyte response, this study evaluated the effects induced by synthetic hair dye ingredients on the oxidative stress response in HaCaT keratinocytes.…”
mentioning
confidence: 99%
“…Although all the alternative tests for skin sensitization have been validated and recommended for testing of neat chemical substances, their usefulness to predict skin sensitization potential of mixtures is being recently investigated. Novel studies comprise the opportunity of optimization for testing of botanical extracts and ingredients (Gan et al, 2013;Moreira et al, 2017, Nishijo et al, 2019, mixtures, and finished products (Settivari et al, 2015;de Ávila et al, 2019de Ávila et al, , Cottrez et al, 2020. For example, the applicability of KeratinoSens TM (OECD 442D) has been evaluated recently for assessment of plant extracts, which were negative in the test but positive when enriched with known sensitizers.…”
Section: Altex Preprint Publishedmentioning
confidence: 99%